The many ages of man: diverse approaches to assessing ageing-related biological and psychological measures and their relationship to chronological age. Issue 2 (March 2019) - Foo, Heidi; Mather, Karen A.; Thalamuthu, Anbupalam; Sachdev, Perminder S.
Abstract : Purpose of review: Chronological age is a crude measure and may not be the best indicator of the ageing process. Establishing valid and reliable biomarkers to understand the true effect of ageing is of great interest. We provide an overview of biological and psychological characteristics that change with age and can potentially serve as markers of the ageing process, and discuss if an integration of these characteristics may more accurately measure the true age of a person. We also describe the clinicopathological continuum of these ageing-related changes. Recent findings: Ageing-related changes in the biological and psychological systems of the body have been studied to varying degrees and with differing emphases. Despite the development of ageing indices, there is no single indicator that can holistically estimate the ageing process. Differential ageing of bodily systems remains poorly understood, and valid methods have not been developed for composite markers of biological and psychological processes. Summary: The ageing process is complex and heterogeneous. Incorporating biological and psychological measures may improve accuracy in reflecting an individual's 'true age, ' and elucidate why some people age successfully, whereas others show ageing-related decline and disease.